Religion and Politics in the East African Revival. (October 2019) - Bruner, Jason
This article briefly describes what was at stake for European missionaries, British colonial officials, and African converts in maintaining a distinction between religion and politics with respect to the East African Revival in Uganda. Focusing upon the years 1935–70, it problematizes clear distinctions between religion and politics by using Derek Peterson's work on the revival as an expression of dissenting politics. The article argues that "religion" and "politics" were both emic categories with contextualized referents, as well as analytic categories with comparative implications.